Global associations between air pollutants and Chronic Obstructive Pulmonary Disease (COPD) exacerbations: a systematic review - Moore,EA; Chatzidiakou,L; Kuku,M-O; Jones,RL; Smeeth,L; Beevers,S; Kelly,FJ; Barratt,B; Quint,JK (European Respiratory Society, 2016)
Background: COPD exacerbations (AECOPD) affect lung function decline and quality of life. The effect of exposure to different air pollutants on AECOPD is unclear.Aim: We systematically reviewed the literature examining associations between air pollutants and hospital admissions for AECOPD.Methods: MEDLINE, EMBASE, BIOSIS & Science Citation Index were searched until September 2015. Inclusion criteria focused on studies presenting solely a COPD outcome defined by hospital admissions, and a measure of gaseous air pollutants and particle fractions. The association between each pollutant with COPD admissions was investigated in meta-analyses using random-effects models. Analyses were stratified by geographical clusters to investigate the evidence worldwide.Results: 46 studies were included and results showed marginal positive associations. The number of included studies was small with high heterogeneity between them and there was evidence of small-study bias. Geographical clustering of the effects of pollution on COPD hospital admissions was evident and reduced heterogeneity significantly. The most consistent association was between a 1mg/m3 increase in carbon monoxide levels with COPD related admissions; Odds Ratio: 1.2 (95%CI: 1.01-1.03).Conclusions: There is mixed evidence on the effects of pollution on AECOPD. Limitations of previous studies include the low spatio-temporal resolution of pollutants, inadequate control for confounding factors, and the use of aggregated health data that ignore personal characteristics. The need for personal exposure monitoring in a large number of geographical locations is evident.